2002
DOI: 10.1046/j.1570-7458.2002.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering of the sycamore aphid, Drepanosiphum platanoidis

Abstract: Spatial and temporal aspects of overwintering in the holocyclic sycamore aphid Drepanosiphum platanoidis (Schrank) (Homoptera: Callaphididae) were investigated. Eggs of D. platanoidis were principally laid on trunks and branches of Acer pseudoplatanus L., at considerable distances from the buds. Trunks with rough bark, followed by branches with moderate roughness supported more overwintering eggs than the relatively exposed smooth surfaces of twigs and terminal buds. Eggs were aggregated on rough bark. Aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 39 publications
(62 reference statements)
0
1
1
Order By: Relevance
“…Unlike other studies that indicated high overwintering mortality of aphid eggs (Leather et al 1995;Wade & Leather 2002), no obvious mortality of eggs was observed in this study. Since larval syrphids are the primary predators of the maple aphid in spring at the study sites, the eggs of syrphids were regularly removed from the study saplings whenever they were found in order to prevent predation of newly-hatched aphids.…”
Section: Aterials and M Ethodscontrasting
confidence: 97%
“…Unlike other studies that indicated high overwintering mortality of aphid eggs (Leather et al 1995;Wade & Leather 2002), no obvious mortality of eggs was observed in this study. Since larval syrphids are the primary predators of the maple aphid in spring at the study sites, the eggs of syrphids were regularly removed from the study saplings whenever they were found in order to prevent predation of newly-hatched aphids.…”
Section: Aterials and M Ethodscontrasting
confidence: 97%
“…Overwinter survival is a significant challenge to aphids, which have adapted different strategies to deal with it. Most aphids overwinter as eggs, which may reach super-cooling points of −42 °C [ 30 ], that are laid on woody host plants, as is the case for the cherry aphid Rhopalosiphum padi (Linnaeus, 1758) [ 31 , 32 ], or in bark crevices, or even in lichens growing on the bark, as reported for the sycamore aphid Drepanosiphum platanoidis (Schrank, 1801) [ 33 ]. The egg-laying stage, in which both parthenogenesis and sexual reproduction coexist (holocyclic), is a part of a complex life cycle adopted by most aphids to pass the winter: this stage consists of one generation of sexual morphs (sexuals) and several generations in which only parthenogenetic females are produced [ 34 ].…”
Section: Introductionmentioning
confidence: 99%